2002
DOI: 10.1152/ajplung.00148.2001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein kinase A accelerates bovine bronchial epithelial cell migration

Abstract: Bronchial epithelial cell migration is required for the repair of damaged airway epithelium. We hypothesized that bronchial epithelial cell migration during wound repair is influenced by cAMP and the activity of its cyclic nucleotide-dependent protein kinase, protein kinase A (PKA). We found that, when confluent monolayers of bronchial epithelial cells are wounded, an increase in PKA activity occurs. Augmentation of PKA activity with a cell-permeable analog of cAMP, dibutyryl adenosine 3',5'-cyclic monophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 46 publications
5
52
1
Order By: Relevance
“…Moreover, the effects of cAMP-dependent PKA activation on migration appear to be cell type-specific. Whereas in the majority of cell types PKA activation inhibits cell migration, PKA activation accelerates the migration of bronchial epithelial cells during wound repair by reducing the levels of active Rho and the formation of focal adhesion (66). On the other hand, it was recently reported that even in fibroblastic cells ␤-adrenoreceptor-mediated signaling had an Src-dependent promigratory effect (62).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effects of cAMP-dependent PKA activation on migration appear to be cell type-specific. Whereas in the majority of cell types PKA activation inhibits cell migration, PKA activation accelerates the migration of bronchial epithelial cells during wound repair by reducing the levels of active Rho and the formation of focal adhesion (66). On the other hand, it was recently reported that even in fibroblastic cells ␤-adrenoreceptor-mediated signaling had an Src-dependent promigratory effect (62).…”
Section: Discussionmentioning
confidence: 99%
“…␤-AR agonists decrease the re-epithelialization of both human and murine skin wounds (Pullar et al, 2006). As multiple cell types contribute to cutaneous wound healing (Martin, 1997) and ␤-AR activation can result in diametrically opposing responses in different cell types (Masur et al, 2001;Murphy et al, 1998;Salathe, 2002;Spurzem et al, 2002), it was important to examine the response to ␤2-AR activation in other cutaneous cells. Here we demonstrate the unique effects of ␤2-AR activation on the physiological processes that contribute to the fibroblasts reparative role in the skin: migration, proliferation and contractile ability.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have investigated the role of ␤-ARs in epithelial wound healing and migration, but the results have been paradoxical. ␤-Antagonists have been reported to either delay (17,18) or enhance (19) corneal epithelial wound healing, and ␤-agonists can stimulate proliferation and migration of transformed corneal epithelial cells (20), SW 480 colon carcinoma cells (21), and bovine bronchial epithelial cells (22). Conversely, ␤-AR agonists delay wound healing in the hind limbs of adult newts (23) and inhibit neutrophil chemotaxis to the lungs (24).…”
mentioning
confidence: 99%